The Effects of a School-Based Mental Health Program on Students’ Knowledge, Behavior, and Depression: A Quasi-Experimental Study in Four Indonesian High Schools - Suryaputri, Indri Yunita; Mubasyiroh, Rofingatul; Arfines, Prisca Petty; Rachmalina, Rika; Idaiani, Sri; Sitorus, Nikson; Rosha, Bunga Ch; Nur Khotimah, Enung; Setiyawati, Diana (Journal of Population and Social Studies [JPSS], 2023)
Schools play a crucial role in promoting the mental health of children and adolescents. This study aimed to examine the effectiveness of a mental health program by evaluating changes in knowledge, behavior, and mental health outcomes of students before and after the intervention. The study employed a pre-and-post-test quasi-experimental approach in four selected high schools in Bogor. It evaluated changes in knowledge, behavior, and mental health outcomes of students pre-and-post the intervention. The study assessed mental health literacy, anti-bullying education, and creating a positive school environment. Data were collected in July and October 2019, with 476 out of 495 students completing both pre- and post-tests. In the intervention group, there was an improvement in knowledge, as evidenced by a decrease in the risk of “having a lack of knowledge” from the pre-test (OR = 1.8, 95% CI [1.2, 2.6], p = .004) to the post-test (OR = 1.2, 95% CI [0.9, 1.8], p = .284). During the pre-test period, students in the intervention schools had a higher risk of experiencing bullying (OR = 1.4, 95% CI [0.9, 2.3], p = .133). However, after the intervention, their risk of being bullied decreased (OR = 0.9, 95% CI [0.6, 1.6], p = .810). The risk of having no peer support also decreased from OR = 1.6, 95% CI [0.5, 5.8], p = .467 to OR = 1.1, 95% CI [0.3, 4.3], p = .933. The condition of depression in the intervention group improved, with an OR = 1.0, 95% CI [0.6, 1.8], p = .924 at the pre-test and an OR = 0.8, 95% CI [0.4, 1.6], p = .511 at the post-test. These findings underscore the significance of initiatives focused on improving student mental health.